Immunologic and Hormonal Effects of Prophylthiouracil Treatment Using Maintenance Dose in Graves’ Disease Patients - Eva Decroli; Asman Manaf; Syafril Syahbuddin (Acta Medica Indonesiana, 2014)
Aim: to assess immunologic remission in patients with Graves’ disease following euthyroid condition at the end of treatment with maintenance dose of PTU. Methods: this is an intervention study using one-group pre-post design. Subjects were 25 Graves‘ disease patients visiting Metabolic Endocrinology Clinic at Dr. M.Djamil hospital Padang and met the inclusion criteria. Patients were given PTU treatment for 12 months. Blood samples were taken at the beginning and at the end of treatment to determine immunological remission reflected by differences in IL-4serum levels. Results: after maintenance therapy, we found significant decrease of T3 levels (2.29±0.57 nmol/L vs. 1.87±0.34 nmol/L, p<0.05), significant decrease of T4 levels (118.15±25.99 nmol/L vs. 94.15±23.76 nmol/L, p<0.05), significant increase of TSH levels (0.379±0.548 vs. 0.859±0.990, p<0.05) and significant decreased levels of IL-4 (12.23±5.74 vs. 3.84±0.42, p<0.05). The IL-4 level, however, did not decrease to the normal levels. Conclusion: PTU administration in maintenance dose can significantly reduce thyroid hormonal parameter levels down to euthyroid condition, but cannot reduce immunological parameter (IL4) to normal limit.